ONLINE DISPUTE RESOLUTION (ODR): PROSPEK PENYELESAIAN SENGKETA E-COMMERCE DI INDONESIA - Meline Gerarita Sitompul; M. Syaifuddin; Annalisa Yahanan (Prima Center Indonesia, 2016)
Internet is not just limited to use of information that can be accessed through social media, but also can be used as a means to trade, that is e-commerce. In cyberspace, e-commerce transactions, it is possible occur a dispute as well as dispute occur in a conventionally legal relation. As activities of trade and e-commerce grow, the frequency of dispute will getting high and it means there will be a dispute that must be solved. Evolving information and communication technologies (ICT) will improve the managing and solving disputes online. When Alternative Dispute Resolution (ADR) are combined with ICT, the result is Online Dispute Resolution (ODR). This research is an attempt to discuss some issues about business settlement via ODR, and the prospect of ODR in Indonesia. This description is an attempt to give comprehensive view about the ODR and how the law will be used to mediate the civil dispute using the internet media as alternative possibility to resolve civil conflict in Indonesian society. This research characteristic is analytical descriptive. In the future, this discussion will open a new way in facilitating Indonesian people, especially for they that seeking the justice provision, in the resolving their dispute using the ODR.Key Words: e-commerce, online dispute resolution, dispute